Framing Behaviours in Novice Interaction Designers - Lotz, Nicole; Sharp, Helen; Woodroffe, Mark; Blyth, Richard; Rajah, Dino; Ranganai, Turugare (Design and Technology Education: An International Journal, 2015)
Framing design problems and solutions has been recognised in design studies as a central designerly activity. Some recent findings with expert designers relate framing practices to problem–solution co-evolution and analogy use, two further widely recognised design strategies. We wanted to understand if interaction design novices also use co-evolution and analogies to frame their thinking. Furthermore we wanted to see if there are any differences across cultures. The paper reports an analysis of data gained from protocol studies with novice interaction designers in the UK and Botswana. Novice interaction designers in the UK and Botswana show some similarities in framing behaviours using co-evolution and opening analogies to develop metaphorical themes in framing. But within these observations we also found differences across the cohorts, such as different numbers of co-evolution episodes or opening analogies. The implications are discussed in the light of adopting appropriate design pedagogy for novices in different cultures. To increase reframing and generation of more ideas in UK design novices, educators would need to increase the number of leaps between problem and solution spaces. To encourage Botswana groups to frame ideas and work them through in depth, educators would need to discourage students from building too many bridges. Educators are also encouraged to experiment with prohibiting opening analogies to see what other framing behaviours occur.